The impact of dark chocolate intake on arterial elasticity in individuals with HIV/AIDS undergoing ART: a randomized, double-blind, crossover trial. Issue 6 (17th May 2017) - Teixeira, Andrea Mariana Nunes da Costa; Luzia, Liania Alves; de Souza, Suelen Jorge; de Almeida Petrilli, Aline; Pontilho, Patrícia de Moraes; de Souza, Jose Maria Pacheco; Segurado, Aluísio Augusto Cotrim; Efraim, Priscila; Picone, Camila de Melo; Rondo, Patrícia Helen de Carvalho
Abstract : An increase in the frequency of cardiovascular diseases has been observed in the HIV/AIDS population. Abstract : An increase in the frequency of cardiovascular diseases has been observed in the HIV/AIDS population. Studies involving healthy subjects or subjects with other diseases have shown benefits of chocolate supplementation on endothelial function and vasodilation. We evaluate the impact of chocolate consumption on arterial elasticity in people living with human immunodeficiency virus – PLHIV. A double-blind, crossover trial including 110 PLHIV (19 to 59 years) on antiretroviral therapy – ART for at least 6 months and with a viral load of <500 copies per mL was conducted. All subjects were randomly assigned to 15-d dietary supplements containing dark chocolate or placebo with a 15-d washout period. Each participant received one of the two sequences: A (dark chocolate, placebo chocolate); B (placebo chocolate, dark chocolate). Arterial elasticity was measured using the HDI/PulseWave™ CR-2000 CardioVascular Profiling System®. Body composition, lipid profile, C-reactive protein, and thiobarbituric acid reactive substances were also assessed. Analysis of variance (ANOVA) for repeated measures using the Stata 11.0® program was used for cross-over analysis. Most subjects were men (59.0%) and Caucasian (46.1%) and the mean age was 44.6 ± 7.1 years. The mean time since diagnosis of HIV infection was 13.7 ± 5.3 years and the mean duration of ART was 12.9 ± 4.2 years. Chocolate consumption resulted in significant alterations in the large artery elasticity index – LAEI ( p = 0.049) and the mean concentration of HDL-c was higher after supplementation with dark chocolate ( p = 0.045). This is the first study to evaluate the effect of chocolate on arterial elasticity in PLHIV. The results showed that dark chocolate consumption for 15 days improved the elastic properties of the LAEI in PLHIV. These findings, added to the noninvasive method used, may expand the knowledge of CVDs in this population.